Blackmailing Lobbyists - Maik Schneider (Verein für Socialpolitik, 2010)
We examine lobby influence on policy outcomes in a legislative vote-buying model with two competing lobbyists and endogenous policy proposals. We compare two polar cases: (1) the committee or (2) the lobbyist seeking policy change writes the bill. Surprisingly we find that if the salience of the issue is low, the committee proposes more extreme policy changes than the pro-policy-change lobbyist even though the policy preferences of the committee are more moderate. The opposite is true if salience is high. We also show that the extreme proposals when salience is low do not necessarily involve lower welfare relative to the lobbyist's proposal.
Keywords: D72; P16; D70; 330; legislative lobbying; vote buying; legislatures; political economy